Development and application of a multi-scalar, participant-driven water poverty index in post-tsunami India. Issue 6 (2nd November 2017) - Juran, Luke; MacDonald, Morgan C.; Basu, Nandita B.; Hubbard, Shane; Rajagopal, Raj; Rajagopalan, Prema; Philip, Ligy
Abstract: This article presents a modified water poverty index that captures several waterscape attributes to better understand complex issues surrounding water. Household surveys ( n = 300), water quality tests ( n = 375) and qualitative methods were deployed to examine 14 post-tsunami settlements in Nagapattinam and Karaikal Districts (India) through the lens of water. Data were used to develop a contextualized, participant-driven water poverty index to measure water poverty at several scales. Statistical tests revealed significant differences between the two districts ( p ≤ .0001) and between rural and urban areas within each district ( p ≤ .0001). Three weight schemes (one dictated entirely by research participants) produced analogous outcomes though predicated on different indicator arrangements.